Change communication strategy in media campaigns and Covid-19 rising infections in Nigeria - Stanislaus Iyorza; Leonard Ojorgu (International Journal of Humanities and Innovation (IJHI), 2020)
This paper seeks to investigate the relationship between change communication approaches and rising infections in Covid-19 in Nigeria. There are heavily sponsored media campaigns for disease prevention in media advocacy and social mobilization by media organizations, Government and Non-Governmental Organizations, but cases of infections have been on the steady rise. Being correlational research, this study adopts a survey design, using quantitative and qualitative methods to elicit data from the study population. The population of this study included five (5) university Professors and three (3) media practitioners who responded in a personal communication on why media campaign for disease prevention is not as successful as intended, and 334 respondents whose reactions to the change communication approaches in media campaigns in cases of Covid-19 were examined. Findings revealed that most Nigerians were not responding adequately to the change communication strategy and preventive message campaign appeals to wash their hands thoroughly under running water, avoid crowded spaces, and use hand sanitizers. Findings also revealed that the nonavailability of the materials and products such as running taps and the high cost of hand sanitizers militated against the people's ability to act. The study recommended that the Federal Government make available all that the people needed to comply with the messages by creating the deserved enabling environment. Simultaneously, communication strategists should use the appropriate language and appeals that are compatible with the plight of the people.